Combination of nucleated red blood cells and inflammatory biomarkers (PCT and CRP) for predicting sepsis and septic shock in children - Pu, Kaibin; Wang, Chunyi; Cheng, Jie; Chen, Dapeng; Tan, Liping; Tan, Jihong; Li, Hongdong (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionSepsis remains a leading cause of mortality and morbidity worldwide. This study aimed to investigate the clinical characteristics of children with sepsis and septic shock, with emphasis to evaluate the predictive value of C-reactive protein (CRP), procalcitonin (PCT), and nucleated red blood cell (NRBC) count in pediatric sepsis and septic shock patients.MethodsWe included a total of 121 children, including 80 with sepsis and 41 with septic shock, who were admitted to the Children’s Hospital of Chongqing Medical University between January 2021 and June 2024.ResultsNo significant differences in sex, age, weight, or basic diseases were observed between the sepsis and septic shock groups (P > 0.05). However, the laboratory findings showed significantly lower platelet counts and hemoglobin levels as well as higher CRP, PCT, NRBC, lactic acid, ALT, CK-MB, urea nitrogen, and APTT levels in the septic shock group (P < 0.05). Poorer outcomes were observed in the septic shock group, with higher rates of disease progression or death (63.4% vs. 31.2%, P < 0.05). ROC analysis showed that the combination of these three biomarkers achieved greater predictive accuracy (AUC = 0.956), outperforming CRP and PCT alone. Compared with those with sepsis, children with septic shock presented worse clinical and laboratory profiles, required more intensive treatments, and had poorer outcomes.ConclussionThe inclusion of the NRBC count, combined with CRP and PCT, significantly increases the predictive efficacy of disease severity or progression, particularly indicative of septic shock, highlighting the potential of this combination for early diagnosis and management in pediatric patients.